Treatment seeking behavior and level of treatment among brick kiln workers: A Study in Azamgarh District, Uttar Pradesh - Kumar Parimal Shrestha; Harihar Sahoo; Mrinmoy Pratim Bharadwaz (Elsevier, 2021)
Background: Brick kiln industries are usually located at remote locations due to which labors feel difficulties to even fulfill their basic needs. They are bound to buy their requirements from assigned suppliers. In order to receive treatment, labors don't find much of the options to choose. This study tends to examine the treatment seeking behavior and their level of treatment among brick kiln workers. Method: A structured interview and in-depth interviews were used for data. Data entry was done in SPSS version 23. Data was analyzed using STATA version 15. Result: Total of 450 respondents, 82.7% suffered from musculoskeletal disorder, and 53.8% suffered from respiratory disease and similar number of molders were suffering from aforementioned diseases. More than 30% of workers suffered from eye disease and skin disease in 36-50 years of age category. In the study, 95% workers were suffering from occupational morbidity. Out of which 92.5% reported utilization of outpatient care, whereas, 7% of non-users stated, primary reason for not using health care services were, low financial support, unawareness of health centers, tight working hours. Conclusion: The prevalence of occupational morbidity is high whereas, treatment seeking among workers are not satisfying. Treatment seeking among labors is found to be delayed and above all, labors are highly ignorant about symptoms. Due to low income, low education and skills, deprived workers are considered for low grade and poorly paid jobs in the kilns where they are victimized by their employer and ill treatment regarding salary and wages were also observed.